The Mix of Military and Civilian Faculty at the United States Air Force Academy Finding a Sustainable Balance for Enduring Success - Keller, Kirsten M. (RAND Corporation, 2013)
This report examines how changes to the current military-civilian faculty composition at the United States Air Force Academy might affect cadets' officership and academic development, cost, staffing challenges, and officer career development. Based on the study's findings, the report makes recommendations for a faculty composition that best balances these key factors and is sustainable into the future.